2022
DOI: 10.5334/gh.1148
|View full text |Cite
|
Sign up to set email alerts
|

WHO Non-Lab-Based CVD Risk Assessment: A Reliable Measure in a North Indian Population

Abstract: Introduction: Timely, affordable, and sustained interventions reduce the risk of heart attack or Stroke in people with a high total risk of cardiovascular diseases (CVD). Risk prediction tools are available to estimate the cardiovascular risk using information on multiple variables. CVD risk charts prepared by the World Health Organization (WHO) has laboratory-based and non-laboratory-based charts with the latter meant for use in resource limited settings. We conducted a study to determine concordance between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…This is useful in setting with poor availability of laboratory services. A study conducted in North India showed good agreement between the WHO laboratory and non-laboratory CVD risk score [ 13 ]. BP and FBS/RBS were measured monthly at each follow-up visit.…”
Section: Methodsmentioning
confidence: 99%
“…This is useful in setting with poor availability of laboratory services. A study conducted in North India showed good agreement between the WHO laboratory and non-laboratory CVD risk score [ 13 ]. BP and FBS/RBS were measured monthly at each follow-up visit.…”
Section: Methodsmentioning
confidence: 99%
“…In this area, the TB treatment LTFU has previously been found to be between 11% and 14%,[ 3 6 ] and the current alcohol consumption among men has been reported to be 30% (in stark contrast to current alcohol use among women—0.2%). [ 13 14 ] Two out of nine TUs of district Faridabad viz. TUs Ballabgarh and Mohna were purposively selected.…”
Section: Ethodologymentioning
confidence: 99%
“…In limited resource settings like Nepal where there is limited availability of laboratory facilities, a nonlaboratory‐based CVD risk prediction chart can be used as an appropriate tool for estimating the risk of CVDs. Many studies have already reported that nonlaboratory‐based WHO/ISH risk prediction charts work almost as accurately as laboratory‐based prediction charts 9,12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Other examples of CVD risk prediction charts are PROCAM, Systematic Coronary Risk Evaluation (SCORE), Reynold Risk Score, QRISK, and so forth. However, the majority of these charts are based on developed high‐income countries thus they may not be applicable in settings with low resources 9,10 . In 2007, the WHO in collaboration with the International Society of Hypertension (ISH) developed a risk prediction chart for estimating the 10‐year risk of major fatal or nonfatal cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation